Nanoparticle Vaccines for Inducing HIV-1 Neutralizing Antibodies - Mitch Brinkkemper; Kwinten Sliepen (Vaccines, 2019)
The enormous sequence diversity between human immunodeficiency virus type 1 (HIV-1) strains poses a major roadblock for generating a broadly protective vaccine. Many experimental HIV-1 vaccine efforts are therefore aimed at eliciting broadly neutralizing antibodies (bNAbs) that are capable of neutralizing the majority of circulating HIV-1 strains. The envelope glycoprotein (Env) trimer on the viral membrane is the sole target of bNAbs and the key component of vaccination approaches aimed at eliciting bNAbs. Multimeric presentation of Env on nanoparticles often plays a critical role in these strategies. Here, we will discuss the different aspects of nanoparticles in Env vaccination, including recent insights in immunological processes underlying their perceived advantages, the different nanoparticle platforms and the various immunogenicity studies that employed nanoparticles to improve (neutralizing) antibody responses against Env.